Reforming Qardh Practices in Islamic Banking: A Critical Analysis Based on Jasser Auda’s Maqāṣid al-Sharīah Systems Approach in Indonesia - Mohammad Ghozali; Khusniati Rofiah; Khurun'in Zahro'; Mualimin Mochammad Sahid (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines the extent to which qardh contracts in Indonesian Islamic banking align with the higher objectives of shariah (maqasid) as conceptualised in Jasser Auda’s systems-based framework. The research addresses a gap in the existing literature, where qardh is often analysed in terms of legal-formal compliance without a critical assessment of its multidimensional ethical and social functions. The research adopts a qualitative-normative approach, utilising library research to analyse primary sources from classical fiqh, Qur’anic verses, hadiths, fatwas, and relevant regulatory texts, as well as secondary scholarly literature on qardh and Maqasid al-Shari'ah. Jasser Auda’s multidimensional maqasid framework serves as the primary analytical tool. The study reveals a significant disparity between the ideal concept of qardh as a benevolent, non-profit financial instrument and its current implementation in Indonesia, which frequently includes administrative charges, restrictive eligibility criteria, and limited outreach. Through Auda’s systems approach, the research demonstrates that properly designed qardh contracts can fulfil five maqasid dimensions: protection of wealth (equitable resource access), protection of life (emergency aid), protection of intellect (educational funding), protection of lineage (family economic support), and protection of religion (ethical lending). This study offers a conceptual reform model for aligning qardh practices with maqasid-oriented policies and product designs. It advances Islamic finance scholarship by shifting the discourse from procedural compliance toward holistic socio-economic transformation, positioning Islamic banking as a genuine instrument for justice and inclusion in Indonesia.